The importance of maqasid syariah in the formation of state government policy - Muhammad Husni, Ahmad (SAS Publishers, India, 2018)
In order to ensure that all the policies taken meet the Islamic principles, the Ulama’ decided some methods and rules should be adhered to while implementing any laws. Knowledge about maqasid syariah need to be fully understood and applied it accordingly to ensure all the regulations implemented as according to the Islamic shari’a. The main purpose of this article is to analyze the importance of maqasid syariah in the field of siyasah shar’iyyah , which considered as among the most essential recommendation in the formulation of siyasah guidelines in the administration of an Islamic country. This writing uses the analysis method of document to review on how the maqasid is taken into account to set up the laws that related to siyasah shar’iyyah. This article concludes that the stages of maqasid should be consider to come to a decision about the weight of significance when the opposition between the maqasid happen.